Environmental Management in Fishery Harbour (Case Study of “Pelabuhan Perikanan Nusantara Palabuhanratu”, Sukabumi Regency, West Java Province - Risnandar, Risnandar (Journal of Fisheries Resources Utilization Management and Technology, 2013)
Environmental management in fishery harbour was studied in PPN Palabuhanratu. The study was mainly based on the survey methodological. The data collected based on primary and secondary data. Field observation was conducted to determine physico-chemical characteristics and biological characteristics of the benthos and plankton, depth interview with the fishermans and stakeholders of PPN Palaburanratu and identify of existing environmental management facility in PPN Palaburanratu. In generally the available facilities and environmental management in PPN Palabuhanratu focused on environment cleaning from solid waste. The Pollution Index and STORET analysis of surface water quality from 7 sampling point in the PPN Palabuhanratu area categorize as polluted indicated by quite high ammonia at St. 5, St 6 and St.7. The plankton analysis community saprobic index was in the phase of β-mesosaprobic to polysaprobic indicating low to heavy level pollutions with few organic and anorganic contaminant substance. PPN Palabuhanratu has already conducted standar environmental management. However the efforts standard regulations or procedures still not comply with that stated by Misnistry of Environment.